"Fourteen Dollars for One Beer!" Pre‐drinking is associated with high‐risk drinking among Victorian young adults. (December 2013) - MacLean, Sarah; Callinan, Sarah
Abstract Objective : Pre‐drinking entails consuming alcohol before attending licensed venues. We examined the relationship between pre‐drinking, intention to get drunk and high‐risk drinking among Victorians aged 18–24 years, to consider whether reducing pre‐drinking might ameliorate alcohol‐related harm. Methods : Variables within the 2009 Victorian Youth Alcohol and Drugs Survey (VYADS) dataset were analysed and compared with a thematic interpretation of research interviews involving 60 young adults living in Melbourne. High‐risk drinking was defined as consuming 11 or more standard drinks in a session at least monthly. Results : VYADS data show that pre‐drinking was a significant predictor of high‐risk drinking, even after intention to get drunk was controlled for. The most common explanation provided by interviewees for pre‐drinking was because it is cheaper to purchase alcohol at bottle shops than at bars and clubs. This was particularly emphasised by those who drank at a high‐risk level. Conclusions : The study suggests that people pre‐drink because they desire to be intoxicated, but also that pre‐drinking patterns and product choices exacerbate the likelihood of high‐risk drinking. Reducing availability of cheap packaged alcohol has potential to limit both pre‐drinking and high‐risk drinking among Victorian young adults. Implications : The study adds weight to calls to implement minimum alcohol pricing in Australia.